DISCIPLINE OF E-KINERJA APPLICATION USAGE FOR STATE CIVIL APPARATUS AT THE BUREAU OF ECONOMY AND DEVELOPMENT ADMINISTRATION OF THE SETDA OF SOUTH SULAWESI PROVINCE - A. Putri Pratiwi Harsan; Haedar Akib; Asri Nur Aina (Jurnal Aktor, 2026)
This study aims to find out the Discipline of Using the E-Performance Application for ASN in supporting the assessment of superiors. This research includes qualitative descriptive research with data collection techniques through observation, interviews and documentation. The data analysis technique uses data condensation, data presentation, and conclusion drawn. The results of this study show that the assessment carried out by the boss has gone well through this application using the theory of Performance Assessment indicators, work quality, work quantity, time period, workplace attendance, and cooperative attitude. However, in filling the workload carried out by employees is still not optimal. It can be seen in indicators, time period and attendance at work. This is because there are still many employees who are not good at utilizing and lack awareness of the importance of time discipline, further efforts need to be made to increase employee awareness and understanding of the importance of e- performance and provide more intensive training so that the use of the application can be more effective and efficient